The optimum size of rotating qarḍ ḥasan savings and credit associations - Kazem Sadr (ISRA International Journal of Islamic Finance, 2017)
Purpose: Several indigenous credit and savings schemes have been accredited recently in developing countries for the benefit of households and entrepreneurs alike. Famous among them are the Rotating Savings and Credit Associations (ROSCAs) that exist in almost all continents currently. The rapid development of ROSCAs and their varied structures in many countries have been the subject of numerous studies. What has not been thoroughly analysed is the optimum size of these associations and the fact that lending and borrowing is without interest. The aim of this paper is to present a model that would determine the optimum size of ROSCAs and deal with the following issues: how the group size varies with changes in the income level of the members, the demand for the loan, the size of the collected loan and its duration. Further, the question of whether or not lending to the association in return for obtaining larger sums is a violation of the qarḍ (loan) contract is dealt with, and several Sharīʿah compatible formulations are provided. Design/methodology/approach: Economic analysis has been applied to show the optimum size of Qarḍ Ḥasan Associations (QHAs), which are the Sharīʿah-compliant equivalent of ROSCAs, and the Sharīʿah rules of the qarḍ contract to illustrate the legitimacy of group lending. Findings: The major findings of this study are determination of the optimum size of QHAs, the factors that affect the size and suggestion of alternative legal forms for group financing. Research limitations/implications: Inaccessibility to sources of data to test the hypothesis that has been put forth is the main difficulty encountered when conducting research on the subject. Practical implications: The paper concludes that the development of informal interest-free ROSCAs in both Muslim and non-Muslim countries is an efficient informal microfinance scheme and that it is compatible with Sharīʿah rules. Originality/value: The optimum size of ROSCAs and QHAs has been presented in this paper.
Keywords: 330; Microfinance; ROSCA; QHA; Optimum size; Qarḍ contract